What Happens at the Polling Place: Using Administrative Data to Look Inside Elections. (30th June 2016) - Burden, Barry C.; Canon, David T.; Mayer, Kenneth R.; Moynihan, Donald P.; Neiheisel, Jacob R.
Abstract: Tremendous attention has been paid to local election administration since the 2000 presidential election meltdown, yet policy makers still lack basic information about what happens at the polling place. One strategy to understand the interactions between citizens and street‐level election bureaucrats is to turn to administrative data. Using logs collected by polling place workers, the authors analyze more than 66, 000 individual incidents recorded from four different statewide elections. Such data provide novel insights and guidance for the administration of elections. Findings indicate that task scale (in terms of the number of ballots) and complexity (in terms of absentee ballots) increase the incident rate. Managerial choices about how polling places are run also matter: the use of electronic voting machines and central count processing of ballots reduce the incident rate, while splitting poll worker shifts increases it. Operator capacity, measured in terms of experience, also reduces the number of incidents . Abstract : Related Content:Newby and Greene (PAR May/June 2017)